Spatio-Temporal Gait Parameters in Association with Medications and Risk of Falls in the Elderly - Gimunová, Marta; Sebera, Martin; Kasović, Mario; Svobodová, Lenka; Vespalec, Tomáš (Clinical interventions in aging, 2022)
Purpose: The aim of this study was to analyze factors affecting spatio-temporal gait parameters in elderly people of both genders and different ages with different risks of fall, fall history, and medications. Patients and Methods: A total of 210 community-dwelling older adults (156 females, 54 males; mean age 72.84±6.26 years) participated in this study. To assess the risk of falls, the Downton Fall Risk Index was used. An additional question about medication intake (all prescribed drugs) was asked. To assess the spatio-temporal gait parameters, the Zebris FDM platform was used. Gait parameters and Downton Fall Risk Index, stratified by participants' history of falls, multiple medication use (0/1/2+), gender, age, and medication categories, were statistically analyzed using the Mann-Whitney U-test and Kruskal-Wallis test. Results: When comparing different medication categories, a Downton Fall Risk Index score indicating a high risk of falls was observed in the psychotropic medication category (3.56±1.67). A gait velocity suggesting a higher risk of falls (≤3.60 km/h) was observed in the psychotropic (2.85±1.09 km/h) and diabetes (2.80±0.81 km/h) medication categories, in the age groups 70-79 years (3.30±0.89 km/h) and 80+ years (2.67±0.88 km/h), and in participants using two or more medications (3.04±0.93 km/h). Conclusion: The results of this study confirm previous observations and show that higher age and multiple medication negatively affect the gait, and that the higher risk of falls is associated with psychotropic and diabetes medication use. These results provide important information for future fall preventive programs for the elderly that would be especially beneficial for elderly people taking psychotropic and diabetes medication.
Keywords: rizikové faktory; Psychotropic Drugs; Gait; Independent Living; Risk Factors; lidé; Female; senioři; mužské pohlaví; Male; Aged; chůze (způsob); samostatný způsob života; psychotropní léky; ženské pohlaví; Humans